Caspase-1 Inflammasome Activation Mediates Homocysteine-Induced Pyrop-Apoptosis in Endothelial Cells. Issue 10 (13th May 2016) - Xi, Hang; Zhang, Yuling; Xu, Yanjie; Yang, William Y.; Jiang, Xiaohua; Sha, Xiaojin; Cheng, Xiaoshu; Wang, Jingfeng; Qin, Xuebin; Yu, Jun; Ji, Yong; Yang, Xiaofeng; et al.
Abstract : Rationale: : Endothelial injury is an initial mechanism mediating cardiovascular disease. Objective: : Here, we investigated the effect of hyperhomocysteinemia on programed cell death in endothelial cells (EC). Methods and Results: : We established a novel flow-cytometric gating method to define pyrotosis (Annexin V − /Propidium iodide + ). In cultured human EC, we found that: (1) homocysteine and lipopolysaccharide individually and synergistically induced inflammatory pyroptotic and noninflammatory apoptotic cell death; (2) homocysteine/lipopolysaccharide induced caspase-1 activation before caspase-8, caspase-9, and caspase-3 activations; (3) caspase-1/caspase-3 inhibitors rescued homocysteine/lipopolysaccharide-induced pyroptosis/apoptosis, but caspase-8/caspase-9 inhibitors had differential rescue effect; (4) homocysteine/lipopolysaccharide-induced nucleotide-binding oligomerization domain, and leucine-rich repeat and pyrin domain containing protein 3 (NLRP3) protein caused NLRP3-containing inflammasome assembly, caspase-1 activation, and interleukin (IL)-1β cleavage/activation; (5) homocysteine/lipopolysaccharide elevated intracellular reactive oxygen species, (6) intracellular oxidative gradient determined cell death destiny as intermediate intracellular reactive oxygen species levels are associated with pyroptosis, whereas high reactive oxygen species corresponded to apoptosis; (7) homocysteine/lipopolysaccharide induced mitochondrial membrane potential collapse and cytochrome- c release, and increased B-cell lymphoma 2–associated X protein/B-cell lymphoma 2 ratio which were attenuated by antioxidants and caspase-1 inhibitor; and (8) antioxidants extracellular superoxide dismutase and catalase prevented homocysteine/lipopolysaccharide -induced caspase-1 activation, mitochondrial dysfunction, and pyroptosis/apoptosis. In cystathionine β-synthase–deficient ( Cbs −/− ) mice, severe hyperhomocysteinemia-induced caspase-1 activation in isolated lung EC and caspase-1 expression in aortic endothelium, and elevated aortic caspase-1, caspase-9 protein/activity and B-cell lymphoma 2–associated X protein/B-cell lymphoma 2 ratio in Cbs −/− aorta and human umbilical vein endothelial cells. Finally, homocysteine-induced DNA fragmentation was reversed in caspase-1 −/− EC. Hyperhomocysteinemia-induced aortic endothelial dysfunction was rescued in caspase-1 −/− and NLRP3 −/− mice. Conclusions: : Hyperhomocysteinemia preferentially induces EC pyroptosis via caspase-1–dependent inflammasome activation leading to endothelial dysfunction. We termed caspase-1 responsive pyroptosis and apoptosis as pyrop-apoptosis. Abstract : Supplemental Digital Content is available in the text.